The Role of Sharing Phase in Think-Pair-Share Technique in Promoting Deep Learning and Student’s Speaking Confidence: A Qualitative Study - Sonya, Putri; Seinsiani, Izzati Gemi (Journal of English Language and Education, 2026)
In the context of global communication, student’s speaking confidence and deep learning have become essential competencies in the  EFL classroom. However, many Indonesia students still experience high affective barriers during speaking activities, while previous studies have largely focused on the overall effectiveness of cooperative strategies rather than specific instructional stages. This study aims to explore the role of the Sharing phase in the Think-Pair-Share technique in promoting deep learning and students’ speaking confidence. Employing a descriptive qualitative design, data were collected through classroom observations, learning experience questionnaires, and semi-structured interviews. The findings reveal that the Sharing phase reduces speaking anxiety through social validation, enhances students’ confidence, and supports deep learning by encouraging idea reconstruction and reflective communication. The study concludes that the Sharing phase functions as a critical pedagogical stage that integrates emotional safety with cognitive development in the EFL speaking classrooms.